A micromechanical approach to evaluate the post-impact residual stiffness of woven composites. (March 2016) - Colombo, Chiara; Vergani, Laura
Woven composites are widely used in the design of lightweight structures. For a proper design and a safe maintenance, it is important to have a database of their mechanical properties in undamaged but also in damaged conditions. In this work, the attention is focused on a textile carbon reinforced composite. The aim is to define post-impact residual stiffness of the composite by means of a simple and quick but efficient approach. Stiffness of the composite is evaluated by two micromechanical approaches, based on the concept of Unit Cell. These approaches are both analytical and numerical, implemented by the finite element method. In case of the material damaged by a low-speed impact, a possible range of degradation of stiffness matrix is provided. Calibration is proposed based on experimental observations. This procedure evaluates damage and residual stiffness starting from the Unit Cell, up to the lamina and then the whole laminate. This information is certainly useful to quickly estimate structural integrity and residual stiffness of post-impacted structures.